Characterization of the human endogenous retrovirus K Gag protein: identification of protease cleavage sites - Kraus, Benjamin (BioMed Central, 2011)
BACKGROUND: Viral genomes of the human endogenous retrovirus K (HERV-K) family are integrated into the human chromosome and are transmitted vertically as Mendelian genes. Although viral particles are released by some transformed cells, they have never been shown to be infectious. In general, gammaretroviruses are produced as immature viral particles by accumulation of the Gag polyproteins at the plasma membrane, which subsequently bud from the cell surface. After release from the cell, Gag is further processed by proteolytic cleavage by the viral protease (PR), which results in morphologically mature particles with condensed cores. The HERV-K Gag polyprotein processing and function has not yet been precisely determined. RESULTS: We generated a recombinant poxvirus, encoding the human endogenous retrovirus K consensus gag-pro-pol genes (MVA-HERV-K(con)) and obtained high levels of HERV-K Gag expression. The resulting retroviral particle assembled at the plasma membrane, as is typical for gammaretroviruses; and immature as well as mature retrovirus-like particles (VLPs) were observed around the infected cells. VLPs were purified, concentrated and separated by two-dimensional gel electrophoresis. The HERV-K Gag fragments were identified by mass spectroscopy and N-terminal sequencing which revealed that HERV-K Gag is processed into MA, a short spacer peptide, p15, CA and NC. CONCLUSION: The cleavage sites of HERV-K Gag were mapped and found to be highly conserved among HERV-K genomes. The consensus HERV-K gag gene used in this study is known to support viral, infectivity [1], and thus the cleavage sites that were mapped in this study for all the Gag components are relevant for HERV-K infectivity.